The Role of Meteorology in the Mining Chain in Northern Brazil - Ferreira, Douglas Silva; Paes, Ana Paula; da Costa, Cláudia Wanzeler; Tedeschi, Renata; Silva Júnior, Renato; Júnior, Wilson Nascimento; Neto, Antônio Nogueira; Kuhn, Paulo; Franco, Vânia; Jesus, Edmir; Souza-Filho, Pedro Walfir; de Souza, Everaldo; et al. (European Journal of Applied Sciences, 2024)
Mining is an important branch of the economy in Brazil. Particularly in the eastern Amazon, a large part of the mineral chain spans regions with heterogeneous landscapes characterized by ridges colonized by native rainforests and canga vegetation, where mining activities have developed, rolling hills with extensive pastures and croplands, and restricted urban areas. Regarding operational activities, the mining industry takes place in open-pit, railway and port settings, all of which are naturally exposed to the impacts of adverse weather conditions. This article addressed the importance of meteorological studies in minimizing and managing the rebounding of atmospheric processes in the mining chain from the mines to the ports. The main methods used in the analyzed studies included regional numerical models and statistical modeling adapted for the target area. The results presented herein refer to the development of climate projections focusing on precipitation extremes, seasonal precipitation forecasts, a short-term meteorological forecasting system, a lightning alert system for mining areas and the creation of a hydrometeorological monitoring network. Such results were presented to stakeholders, who can use information derived from scientific research, especially when planning their respective activities on different time scales, including annual, monthly, daily and hourly timescales, from the perspective of process optimization, human safety, community well-being, biodiversity conservation and water resource management.